A battle for transportation routes in the Russian neighborhood : Is there a place for small states? - Valiyev, Anar (Springer Nature Limited, 2020)
Driven by an increased interest in enhancing connectivity, great powers are in the competition to implement their transportation projects. Meanwhile, small states located in the crossroad of the transportation routes are offered with benefits while facing several challenges. In this regard, the current article studies three major transportation initiatives in the South Caucasus region from both political and economic perspectives. The article will try to analyze how these might challenge the regional hegemony of Russia. Hereinafter, by looking at the case of Azerbaijan, the role of small states throughout this process is identified.
International Politics.
Keywords: States, Small -- Economic conditions; International relations.; Regionalism.; International economic relations.; Caucasus, South -- Economic integration.